The Development of DSG Micro-credential Course Registration System using Laravel Framework - Zulazli, Amirul Hafiz; Nur Ariffin Mohd Zin, (Applied Information Technology And Computer Science, 2025)
The Doctorate Support Group (DSG) Micro-credential Course Registration System addresses the specific needs of DSG's 107,000 members by resolving issues related to the lack of a standardized registration process. This project employs an object-oriented approach to develop a web-based system aimed at enhancing user experience and organizational efficiency. The system features a user-friendly registration and login process, an administrative control panel for managing courses and user activities, a classroom system that allows joining Zoom meetings, and a "My Courses" section that includes learning materials, assignments, and marks. Secure payment processing is integrated with Stripe to ensure safe transactions. The system will undergo thorough alpha and beta testing to ensure it meets user needs and improves satisfaction and efficiency. This project aims to transform DSG's doctoral education support, providing a seamless, scalable, and efficient micro-credential registration platform.